Genome-wide analysis of sugar transporter gene family in Erianthus rufipilus and Saccharum officinarum, expression profiling and identification of transcription factors - Akbar, Sehrish; Hua, Xuiting; Zhang, Yingying; Liu, Gang; Wang, Tianyou; Shi, Huihong; Li, Zhen; Qi, Yiying; Habiba, Habiba; Yao, Wei; Zhang, Mu-Qing; Zhang, Jisen (Frontiers in Plant Science, 2025)
Sugar, the primary product of photosynthesis, is a vital requirement for cell activities. Allocation of sugar from source to sink tissues is facilitated by sugar transporters (ST). These STs belong to the Major Facilitator Superfamily (MFS), the largest family of STs in plants. In this study, we performed genome wide and gene expression data analysis to identify the putative ST genes in Erianthus rufipilus (E. rufipilus) and in Saccharum officinarum (S. officinarum). We identified 78 ST gene families in E. rufipilus and 86 ST gene families in S. officinarum. Phylogenetic analysis distributed the ST genes into eight distinct subfamilies (INT, MST, VGT, pGlcT, PLT, STP, SFP and SUT). Chromosomal distribution of ST genes clustered them on 10 respective chromosomes. Furthermore, synteny analysis with S. spontaneum and Sorghum bicolor (S. bicolor) revealed highly colinear regions. Synonymous and non-synonymous ratio (Ka/Ks) showed purifying selection in gene evolution. Promoter analysis identified several cis-regulatory elements, mainly associated with light responsiveness. We also examined the expression pattern of ST genes in different developing tissues (mature leaf, pre-mature stem, mature stem and seedling stem). Under sugar stress, we identified the significant ST genes showing differential expression patterns. Moreover, our yeast one-hybrid (Y1H) assays identified NAM, ATAF and CUC (NAC) and Lesion Simulating Disease (LSD) potential transcription factors (TFs) that may bind to the SUT1-T1 promoter in S. officinarum, showing negative correlation pattern with SUT1-T1. Our results deepen our understanding of ST gene evolution in Saccharum species and will facilitate the future investigation of functional analysis of the ST gene family.